Rediscovery and complementary description of Amblyseius riodocei El-Banhawy, 1984 (Acari: Phytoseiidae) - Demite, Peterson R.; Santos, Jandir C.; Holtz, Anderson M. (Entomological Communications, 2023)
Amblyseius riodocei El-Banahwy, 1984 (Acari: Phytoseiidae) is rediscovery from material collected in Aracruz, state of Espírito Santo, Brazil. A complementary description is provided with measurements and illustrations of the collected specimen.